Alcohol Deranges Hepatic Lipid Metabolism via Altered Transcriptional Regulation. - Crabb, David W. (American Clinical and Climatological Association, 2004)
Alcohol has classically been thought to cause fatty liver by way of altered redox potential in the liver, which inhibits fatty acid oxidation. Additional effects appear to play a role both in impairing fat oxidation and stimulating lipogenesis. Alcohol reduces the DNA binding and transcription-activating properties of peroxisome proliferator-activated receptor alpha (PPARalpha), both in cultured cells and in mice fed alcohol. Treatment of alcohol-fed mice with a PPARalpha agonist reverses fatty liver despite continued alcohol consumption. Alcohol also activates sterol response element- binding protein 1 (SREBP-1), inducing a battery of lipogenic enzymes. This effect may be due in part to inhibition of AMP-dependent protein kinase. This understanding of alcohol effects provides new therapeutic targets to reverse alcoholic fatty liver.